TRADITIONAL CULTURE ON TELEVISION SCREEN: SEARCH FOR NEW FORMATS IN CONTEMPORARY CHINESE TELEVISION / ТРАДИЦИОННАЯ КУЛЬТУРА НА ТЕЛЕЭКРАНЕ: ПОИСКИ НОВЫХ ФОРМАТОВ НА СОВРЕМЕННОМ ТЕЛЕВИДЕНИИ КИТАЯ - SERGEYEVA T.S. / СЕРГЕЕВА Т.С. (Наука телевидения)
The article discusses the development of enlightenment television, for example, television of China. State initiative is conditioned, due to the requirement for TV stations across the country, to actively create new and original cultural programs that would preserve and spread traditional Chinese culture. So there appeared new programs with high ratings («Hero of Chinese characters», etc.). These projects are a new form of education aimed at familiarizing the youth audience to the national culture.